The influence of retrograde reperfusion on the ischaemia-/ reperfusion injury after liver transplantation in the rat - Kern, Hans (Blackwell Science Inc, 2008)
Dysfunction of the graft after liver transplantation caused by ischaemia-/reperfusion (I/R) injury is a serious clinical problem. The aim of this study was to evaluate the influence of different kinds of reperfusion on I/R injury in a rat model. Arterialized orthoptic rat liver treatment was performed on male LEWIS-(RT(1))-rats. Three groups (n = 7) were formed. Group I: antegrade reperfusion with a 6-min delayed reperfusion via the hepatic artery. Group II: Antegrade reperfusion, simultaneously, via the portal vein and the hepatic artery. Group III: Retrograde reperfusion via the vena cava. Serum parameters were determined one, 24 and 48 h after operation. Furthermore, after 48 h, the liver was taken for histological assessment. After 48 h, rats of group III showed significantly lower aspartate amino transferase and alanine amino transferase serum levels compared with group I and group II rats. Forty-eight hours after transplantation, glutamate dehydrogenase serum level was significantly lower in group III than in group II. In histology, group III livers showed significantly less necrotic spots than group I and group II livers. Maximum size of the necrotic spots was significantly lower in group III than in group I. Also, significantly more necrotic spots were seen in the ‘Rappaport′s zone’ 1 and 2 of group I than in group III. Our data suggested that the expression of I/R-injury correlates with the type of reperfusion. Furthermore, under standard conditions, this study was able to demonstrate that in a rat model, the retrograde reperfusion leads to a lower expression of I/R-injury than the antegrade reperfusion.